KEDUDUKAN DAN PRINSIP PEMBAGIAN ZAKAT DALAM MENGATASI PERMASALAHAN KEMISKINAN (ANALISIS PANDANGAN YUSUF QARDHAWI) - Muhammad Haris Riyaldi (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2017)
Zakat fund is among the sources of funds potentially for overcoming poverty. Fakir and miskin is the preferred class in distribution of zakat funds. This paper aims to explore the views Yusuf Qarhdawi, regarding how to position zakat efforts to overcoming poverty and how the division of zakat right principles that can be being solutions to overcome poverty issues? The study of literature relating with principle of divison of zakat to overcome poverty has implemented, mainly through the works of yusuf qardhawi. Againts the analysis of his views can be stated that the principles relating zakat Islamic sharia hearts overcome poverty. First, Islam makes working is potentially troubleshooting poverty. Second, not all indegent and poor reserves the right to review accept zakat. Meaning indigent and poor not accept entitled to zakat. Third, some of the poor classes helped with zakat funds can be work in order to obtain income (productive), While others were given zakat funds hearts forms consumptive.Dana zakat merupakan diantara sumber dana yang berpotensi untuk mengatasi permasalahan kemiskinan. Fakir dan miskin adalah golongan yang diutamakan dalam pembagian dana zakat. Tulisan ini bertujuan mengupas pandangan Yusuf Qardhawi tentang bagaimana kedudukan zakat dalam upaya mengatasi permasalahan kemiskinan dan bagaimana prinsip pembagian zakat yang tepat sehingga dapat menjadi solusi untuk mengatasi persoalan kemiskinan? Studi literatur berkaitan dengan prinsip pembagian zakat untuk mengatasi kemiskinan telah dilaksanakan, terutama melalui karya-karya Yusuf Qardhawi. Dari analisis terhadap pandangannya dapat dikemukakan beberapa prinsip berkaitan zakat dalam syariah Islam dalam mengatasi kemiskinan. Pertama, Islam menjadikan bekerja sebagai sarana utama dalam mengatasi masalah kemiskinan. Kedua, tidak semua fakir dan miskin berhak untuk menerima zakat, artinya ada fakir dan miskin yang tidak berhak menerima zakat. Ketiga, sebagian golongan fakir miskin dibantu dengan dana zakat supaya dapat bekerja sehingga memperoleh penghasilan (produktif), sedangkan sebagian yang lain diberi dana zakat dalam bentuk konsumtif.